La política exterior rusa pos Guerra Fría. ¿Caso paradigmático de revisionismo? - Adins, Sebastien (2021)
Almost unanimously, official speeches and documents and, at the same time, a large number of academic texts in the West brand Russia as a “revisionist” power. Especially since the annexation of Crimea and Sevastopol by Moscow and the start of the Donbas conflict in 2014, the Eurasian state has been considered as a “spoiler” of international politics, supposedly in search of the weakening of the values, rules and institutions of the so-called “Liberal International Order”. This article aims to problematize this statement by arguing that the category of revisionism does not constitute a one-dimensional international state behaviour, or an objective one. On the other hand, following Murray (2019), revisionism, in addition to its domestic roots, is built through social interactions with other countries, as part of a state’s struggle for recognition. After a review of the literature on this concept and the position of Murray's theory, this article analyses the motives and strategies of Russia in the post-Cold War international order, as well as the capabilities that support its foreign policy. In this light, it will assess the “degree” of revisionism in Russia’s international relations of recent years.